2016
DOI: 10.1016/j.yjmcc.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell-derived inflammatory fibroblasts mediate interstitial fibrosis in the aging heart

Abstract: Pathologic fibrosis in the aging mouse heart is associated with dysregulated resident mesenchymal stem cells (MSC) arising from reduced stemness and aberrant differentiation into dysfunctional inflammatory fibroblasts. Fibroblasts derived from aging MSC secrete higher levels of 1) collagen type 1 (Col1) that directly contributes to fibrosis, 2) monocyte chemoattractant protein-1 (MCP-1) that attracts leukocytes from the blood and 3) interleukin-6 (IL-6) that facilitates transition of monocytes into myeloid fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 87 publications
1
28
0
Order By: Relevance
“…Aging and fibrosis share molecular mechanisms in multiple organs, including the lung [7, 8], heart [9, 10], vascular wall [11], kidney [12], liver [13, 14], and skin [15, 16]. Accumulating literature indicates that SIRTs regulate pathways and molecules involved not only in aging, but also in tissue and organ fibrosis (Table 1).…”
Section: Sirtuins and Tissue Fibrosismentioning
confidence: 99%
“…Aging and fibrosis share molecular mechanisms in multiple organs, including the lung [7, 8], heart [9, 10], vascular wall [11], kidney [12], liver [13, 14], and skin [15, 16]. Accumulating literature indicates that SIRTs regulate pathways and molecules involved not only in aging, but also in tissue and organ fibrosis (Table 1).…”
Section: Sirtuins and Tissue Fibrosismentioning
confidence: 99%
“…RASA1 (RAS p21 protein activator (GTPase-activating protein)), which is also known as p120RasGAP, was the first RasGAP protein identified by researchers and acts mainly by negatively regulating RAS signaling. Recent studies have shown that the RAS signaling pathways may have common pro-fibrotic effects [12-14]. Ana Maria Queirós et al proposed that miRNAs targeting RAS signaling pathway repressor, like RASA1, RASA2, may promote cardiac fibrosis [15].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that collagen is synthesized by fibroblasts; collagen secretion by myocardial fibroblasts directly contributes to cardiac fibrosis [11]. Content of total collagen was measured using a Sircol soluble collagen assay to examine the supernatant of cultured fibroblasts.…”
Section: Resultsmentioning
confidence: 99%